Mendulang Rupiah Di Kawasan Bersejarah Pasca Revitalisasi Kota Lama Semarang Tahun 2017 - Amrillah, M Alam (Jurusan Sejarah Fakultas Ilmu Sosial Universitas Negeri Semarang, 2021)
Revitalization of the old city area is an effort to maintain and preserve historical heritage in city of Semarang. The main problem that will be discussed in this paper is how the economic conditions are affected after the revitalization of informal workers in the old city area. This research, of course, has a purpose, including explaining how the background of the revitalization of the old city, and the changes that occurred afterwards, especially in the economic field and wanting to reveal the reality that occurs in the field by comparing the objectives of the revitalization of the old city. By carrying out historical research methods, this paper finds that the old city, which previously had a face that was not noticed, then became significant after the revitalization in 2017. In addition to knowing the economic conditions after revitalization which had a bad influence, especially on informal workers, with the restructuring of the city. long time was offset by the enforcement of informal workers, such as street vendors. This means that the initial goal of revitalization has not been achieved, namely the welfare of the community. This study reveals some of the progress of revitalization of the old city that has not run optimally